PENGEMBANGAN DASHBOARD INFORMASI SEKOLAH MENENGAH ATAS DI PROVINSI BALI - Qaris Ardian Pratama; I Gede Arta Wibawa; I Wayan Santiyasa (Jurnal Pengabdian Informatika, 2024)
In the rapidly evolving era of information and technology, the Provincial Communication, Informatics, and Statistics Office (Diskominfos) of Bali has a crucial role in managing, developing, and providing information, communication, and statistics in the region. To enhance data accessibility for the public, Diskominfos Bali plans to establish a centralized school information system. This system aims to facilitate stakeholders such as educators, administrators, parents, and the general public in accessing comprehensive and accurate information on school conditions and developments in Bali. By integrating data from various schools, the centralized school information system will provide a holistic view of student data, academic performance, attendance records, school facilities, and other relevant factors. Additionally, the system will be integrated with an interactive and easily comprehensible student dashboard for secondary schools. This dashboard will enable educators and administrators to effectively monitor and analyze student data, including academic achievements, graduation rates, and extracurricular participation. Through the implementation of the centralized school information system and the integrated student dashboard, Diskominfos Bali aims to enhance transparency, efficiency, and the overall quality of education in the region. The system will provide easy access to information for stakeholders and enable data-driven decision-making based on accurate data and informative visualizations.